Institutionalising One-Voice Disaster Press Conferences in Indonesia: A Qualitative Analysis of Policy Effectiveness, Public Information, and Crisis Communication Governance - Bhakti Zaqi Ramadhan; Nurhalimah Firda Agustin; Dwiky Lucky Adiyasha (Universitas Muhammadiyah Jakarta, 2024)
Disaster communication is a critical component of emergency governance, particularly in countries with high exposure to earthquakes, floods, volcanic eruptions, landslides, and tsunamis. In Indonesia, the complexity of disaster management is not limited to emergency response and victim assistance, but also includes the accuracy, consistency, and credibility of public information. This study examines the effectiveness of a one-voice disaster press conference policy in Indonesia, with particular attention to the role of the National Disaster Management Agency (BNPB) as an authoritative communication actor. Using a descriptive qualitative approach, the study draws on observation, interviews, and documentation related to BNPB’s disaster communication practices. Informants include BNPB officials, public relations staff, a media observer, and members of the public. The analysis is guided by four indicators of policy effectiveness: target accuracy, programme socialisation, programme objectives, and programme monitoring. The findings indicate that a one-voice press conference mechanism is essential to reduce misinformation, strengthen public trust, improve coordination between institutions, and ensure that disaster-related information is delivered in a timely, factual, and educational manner. However, the study also identifies several challenges, including fragmented institutional authority, inconsistent media coverage, the rapid circulation of hoaxes on social media, limited public understanding of disaster causes, and the absence of a specific regulatory framework governing one-door disaster press conferences. The article argues that disaster communication in Indonesia requires a more institutionalised, digitally integrated, and legally supported communication model. Such a model should combine official spokesperson authority, media coordination, social media responsiveness, public education, and post-disaster monitoring.